2006
DOI: 10.1016/j.jpubeco.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Tax incidence, majority voting and capital market integration

Abstract: We re-examine, from a political economy perspective, the standard view that higher capital mobility results in lower capital taxes -a view, in fact, that is not confirmed by the available empirical evidence. We show that when a small economy is opened to capital mobility, the change of incidence of a tax on capital -from capital owners to owners of the immobile factor -may interact in such a way with political decision-making so as to cause a rise in the equilibrium tax. This can happen whether or not the fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In such a situation, we could obtain a race to-the-top rather than a race-to-the-bottom in taxes if governments compete by raising taxes to improve the attractiveness of their country through a lower labor cost. A recent paper by Lockwood and Makris (2006) takes a first step toward this direction. They incorporate tax-shifting, heterogeneity between agents within countries and a majority rule decision-making process in a Zodrow and Mieszkowski (1986) tax competition model.…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation, we could obtain a race to-the-top rather than a race-to-the-bottom in taxes if governments compete by raising taxes to improve the attractiveness of their country through a lower labor cost. A recent paper by Lockwood and Makris (2006) takes a first step toward this direction. They incorporate tax-shifting, heterogeneity between agents within countries and a majority rule decision-making process in a Zodrow and Mieszkowski (1986) tax competition model.…”
Section: Discussionmentioning
confidence: 99%
“…This is the total number of votes cast (both valid and invalid) divided by the number of names on the voters' register. We constructed this series using data from the International Institute for Democracy and Electoral Assis-15 Some authors have found that that capital mobility might have no effect on tax rates and that it might even increase them (Lai, 2010 andLockwood andMakris, 2006 and references therein). Our hypothesis is that capital controls will shape the magnitude of fiscal interactions.…”
Section: Political Participationmentioning
confidence: 99%
“… Some authors have found that that capital mobility might have no effect on tax rates and that it might even increase them (Lai, and Lockwood and Makris, and references therein). Our hypothesis is that capital controls will shape the magnitude of fiscal interactions.…”
mentioning
confidence: 99%
“…1 The analysis in ZMW has since been enriched in various directions to provide instances in which capital taxes might be too high. 2 These instances include 3 : trade in capital-and labour-intensive goods (Wilson [43]), large capital-importing countries (DePater and Myers [13]), large foreign ownership of immobile factors (Huizinga and Nielsen [27]), competition for amenities (Noiset [37] and Wooders et al [45]), commonality of the capital tax base between states and federal governments (Keen and Kotsogiannis [30]), government failure (Edwards and Keen [19]), political economy considerations (Fuest and Huber [23], Kessler et al [32], Grazzini and van Ypersele [25] and Lockwood and Makris [34]). …”
Section: Introductionmentioning
confidence: 99%